2003
DOI: 10.1074/jbc.m210828200
|View full text |Cite
|
Sign up to set email alerts
|

Src Kinase Mediates Phosphatidylinositol 3-Kinase/Akt-dependent Rapid Endothelial Nitric-oxide Synthase Activation by Estrogen

Abstract: 17␤-Estradiol activates endothelial nitric oxide synthase (eNOS),The cardioprotective effects of estrogen are diverse, including both rapid non-genomic and delayed genomic effects on the blood vessel wall (reviewed in Ref. 1). Specific, rapid vascular effects, such as moderation of vasomotor tone, have been linked to an estrogen-stimulated increase in bioavailable nitric oxide (NO) 1 (2-4). 17␤-estradiol (E2) treatment of human endothelial cells (EC) induces rapid release of NO by estrogen receptor (ER)-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
227
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(257 citation statements)
references
References 51 publications
(65 reference statements)
26
227
2
1
Order By: Relevance
“…Previous reports have shown that c-Src and the ERa interact in a protein complex (16,18). Therefore, we first sought to determine if the K303R-ERa mutation alters the ability of ERa to bind with c-Src.…”
Section: Results C-src Binds Similar Amounts Of the K303r Mutant Era mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that c-Src and the ERa interact in a protein complex (16,18). Therefore, we first sought to determine if the K303R-ERa mutation alters the ability of ERa to bind with c-Src.…”
Section: Results C-src Binds Similar Amounts Of the K303r Mutant Era mentioning
confidence: 99%
“…It was later shown that estrogen stimulation can activate a number of other classic signal transduction pathways, such as phosphatidylinositol 3-kinase and extracellular signal-regulated kinase 1/2 (16,17), and that ligand-induced ERa activation recruited a c-Src/p85/ERa complex (16,18). In addition to ERa signaling to c-Src, c-Src can phosphorylate ERa on tyrosine 537 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al 2005), while E2 treatment also initiates interaction between ERa, Src and p85, the regulatory subunit of PI3-K (Simoncini et al 2000;Castoria et al 2001). In addition, activation of both ERK and Akt by E2 can be prevented by Src-family kinase inhibitors (PP1 or PP2), which subsequently lead to the blockade of ERK and Akt phosphorylation (Singer et al 1999;Castoria et al 2001;Haynes et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] An example of this is the activation of endothelial nitric oxide synthase (eNOS), which occurs through an IP3-kinase-dependent pathway and is independent of transcription. 9,30 HSP90 is involved in this, because it complexes with eNOS in the cell, and estrogen increases the binding eNOS by HSP90. The exact mechanisms through which this occurs are still being elucidated.…”
Section: Discussionmentioning
confidence: 99%